Stellarator coil optimization towards higher engineering tolerances. (1st August 2018) - Lobsien, Jim-Felix; Drevlak, Michael; Sunn Pedersen, Thomas
Abstract: Recently designed optimized stellarator experiments have suffered from very tight construction tolerances, but some level of deviation of the coil system is unavoidable during fabrication of the coils and assembly of the coil system. In this paper, we present a new approach that incorporates reduced sensitivity to construction tolerances of the coil system into the optimization sequence. The approach was tested within the framework of the existing coil optimization scheme for Wendelstein 7-X. The results are compared with those of a coil set obtained by the original optimization. The result is a more optimal coil system with less stringent tolerances, such that small deviations cause reduced deterioration of the properties important for fusion performance.